2016
DOI: 10.1097/aog.0000000000001680
|View full text |Cite
|
Sign up to set email alerts
|

Prenatally Diagnosed Vasa Previa

Abstract: Planned preterm delivery for women with prenatally diagnosed vasa previa resulted in elective delivery for singletons in 62% and for twins 32%. Gestational age at birth on average was 34.7 weeks for singletons and 32.8 weeks of gestation for twins. Major anomalies were frequent as was respiratory distress syndrome. Elective delivery between 34 and 35 weeks of gestation for singletons is reasonable. As a result of the high rate of nonelective delivery in twins, delivery at 32-34 weeks of gestation may be risk-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 22 publications
2
37
0
Order By: Relevance
“…Therefore, we agree with the proposal that TV-US with Doppler imaging should be carefully performed at about 32nd GW in patients who have a second trimester low-lying placenta [15]. Elective hospitalization and the timing of admission for VP patients remains a matter of debate [7,[15][16][17][18][19][20][21]. It is obvious that inpatient management will increase the chances to monitor uterine activity and abnormal fetal heart rate patterns, and this situation will therefore increase the rate of medical interventions.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Therefore, we agree with the proposal that TV-US with Doppler imaging should be carefully performed at about 32nd GW in patients who have a second trimester low-lying placenta [15]. Elective hospitalization and the timing of admission for VP patients remains a matter of debate [7,[15][16][17][18][19][20][21]. It is obvious that inpatient management will increase the chances to monitor uterine activity and abnormal fetal heart rate patterns, and this situation will therefore increase the rate of medical interventions.…”
Section: Discussionsupporting
confidence: 70%
“…Catanzarite et al reported on the use of tocolytics in 67% of singleton VP cases and 95% of twin VP cases, with the first treatment at 30.6 ± 3.2rd GW, and 26.0 ± 3.3rd GW for Elective hospitalization and the timing of admission for VP patients remains a matter of debate [7,[15][16][17][18][19][20][21]. It is obvious that inpatient management will increase the chances to monitor uterine activity and abnormal fetal heart rate patterns, and this situation will therefore increase the rate of medical interventions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bronsteen et al [2] reported 3 perinatal deaths in 56 patients with a prenatal diagnosis of vasa previa despite emergent delivery. Ca­tanzarite et al [5] reported only 1 perinatal death, which was attributed to cardiac disease, among 96 patients treated over a 12-year period. However, in this series, urgent delivery was required before 34 weeks in 9/77 singletons and 11/19 twins.…”
Section: Commentsmentioning
confidence: 99%
“…The precise distance that these vessels must be from the cervix to be considered a vasa previa is not standardized, although a threshold of within 2 cm has been proposed [1, 2]. Three types of vasa previa have been described [1, 3, 4]: type I occurs when there is a single placental lobe with a velamentous cord insertion; type II occurs when the placenta contains a succenturiate lobe or is multilobed, and fetal vessels connecting 2 lobes course over or near the cervix; and type III occurs when a fetal vessel runs within the membranes over or near the cervix, unassociated with a velamentous cord insertion or bilobed placenta [5]. Because the exposed fetal vessels are neither supported by underlying placenta nor surrounded by Wharton’s jelly, rupture of the fetal membranes may concurrently rupture the vessels resulting in fetal exsanguination and injury or death [3, 4, 6].…”
Section: Introductionmentioning
confidence: 99%